Biobased chemical and energy recovered from waste microbial matrices. (December 2019) - Go, Liew Chien; Fortela, Dhan Lord B; Revellame, Emmanuel; Zappi, Mark; Chirdon, William; Holmes, William; Hernandez, Rafael
Graphical abstract: A Venn diagram of some common waste microbial matrices and their applications as biobased chemical and energy. Abstract : Advancement in bioprocessing has brought 3rd generation biorefineries closer to becoming environmentally and economically sustainable. However, due to the costs and supply reliability of feedstocks, energy consumption, and byproducts cleanup/disposal, it is still economically unfeasible to construct and operate a profitable commercial-scale biorefinery. Integration of microbial biomass within an established distributed infrastructure could provide the foundation of a biorefining industry if numerous products are developed and commercialized. Current peer-reviewed literature offers various technologies to transform microbial biomass from wastewater treatment operations into numerous high-value products and energy. This paper describes some of these opportunities with the goal of envisioning more sustainable and cost-effective wastewater treatment systems. The recovery of resources from waste could be extended to many other systems.